2017
DOI: 10.3390/ijerph14010045
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Transformational Leadership on Safety Climate and Individual Safety Behavior on Construction Sites

Abstract: Unsafe acts contribute dominantly to construction accidents, and increasing safety behavior is essential to reduce accidents. Previous research conceptualized safety behavior as an interaction between proximal individual differences (safety knowledge and safety motivation) and distal contextual factors (leadership and safety climate). However, relatively little empirical research has examined this conceptualization in the construction sector. Given the cultural background of the sample, this study makes a slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 56 publications
3
88
1
3
Order By: Relevance
“…In project-based work environments such as in the 538 construction industry, employees normally have limited direct contact with senior management, while 539 they interact with their supervisors on a daily basis. Therefore, employees are more likely to be 540 Consistent with previous studies (Shen et al 2017;Zohar, 2000), the statistical results in this 550 study provide support that group safety climate and supervisory leadership are two conceptually 551 distinct constructs. Safety climate is workers' perceptions of relative emphasis that a supervisor places 552 on competing goals (e.g.…”
Section: Moderation 485supporting
confidence: 81%
See 1 more Smart Citation
“…In project-based work environments such as in the 538 construction industry, employees normally have limited direct contact with senior management, while 539 they interact with their supervisors on a daily basis. Therefore, employees are more likely to be 540 Consistent with previous studies (Shen et al 2017;Zohar, 2000), the statistical results in this 550 study provide support that group safety climate and supervisory leadership are two conceptually 551 distinct constructs. Safety climate is workers' perceptions of relative emphasis that a supervisor places 552 on competing goals (e.g.…”
Section: Moderation 485supporting
confidence: 81%
“…a 556 specific leadership style) (Zohar, 2000). In addition, supervisory leadership is more relationship-based safety climate is more commitment-based and indicates the consistency in supervisors' safety 559 responses (Zohar and Luria, 2005;Shen et al 2017). Safety climate and supervisory leadership are two 560 independent but related aspects of supervisory behavior (Zohar, 2000).…”
Section: Moderation 485mentioning
confidence: 99%
“…According to Mumford et al (2002), the consequential sharp stage of stimulation is likely to increase innovation of firms. Numerous examples of experimental research support this positive effect of leaders on innovation (Keller 1992;Shen et al 2017;Waldman and Atwater 1994). These studies investigate the association between transformational leadership and innovation generally in research and development (R&D) divisions.…”
Section: Transformational Leadership and Innovationmentioning
confidence: 99%
“…(1) The multi-model CFA method was used to evaluate the discriminant validity of the scale [53,54]: (1) By using the chi-square difference test between each model, which comprised various factors and the benchmark model, the significant discriminant validity was obtained. (2) Determining the fitting index, including degrees of freedom (χ2/df), Tucker-Lewis Index (TLI), comparative fit index (CFI), standardized root mean squared residual (SRMR), and root mean square error of approximation (RMSEA), showed that the fitting index of other models was not remarkable, except for the discriminant validity by Hair et al [51].…”
Section: Reliability and Validitymentioning
confidence: 99%